The prefrontal cortex as an executive, emotional, and social brain - Watanabe, Masataka (Springer, 2017)
This book is devoted to the executive, emotional, social, and integrative functions of the prefrontal cortex (PFC). The PFC has usually been studied only with its executive function or with its emotional function, but recent studies indicate that the PFC plays important roles in integrating executive and emotional functions as well as in social behavior. The first part of the book reviews the functional organization of the PFC in human and nonhuman primates. The subsequent part focuses on the integrator of executive and emotional functions. The third part presents the integrator of executive and social functions, and the final part discusses the default mode of brain activities. There are chapters on animal studies, because functional significance of the PFC cannot be described without referring to those studies. Thus many methodologies are presented such as human neuropsychological, neuroimaging, and stimulation studies, and animal neuropsychological, neurophysiological, neurochemical, neuroanatomical, and neuroimaging studies. Bringing those together, this volume provides a timely and concise picture of the function of the PFC. The result is a valuable resource for students and scientists, providing up-to-date information on this emerging research topic.